ANALISIS KEMAMPUAN KEUANGAN DAERAH DALAM PELAKSANAAN OTONOMI DAERAH (Studi di Kabupaten Bantul Yogyakarta) - setiartiti, lilies (Jurnal Ekonomi & Studi Pembangunan, 2002)
The role of local government in exploring local resource will determine success story of the local government. This study conclude that local government has a high dependence on central government especially in financing routine expenditure of the government. The role of local government can be done by increasing Penerimaan Asli Daerah (PAD).